Determinação das concentrações das atividades de Rádio-226, Rádio-228, e Potássio-40 em diferentes tipos de chás - Silva, Roberto Cruz da (2018)
Tea is an infusion prepared with plant parts such as leaves, flowers and roots, usually prepared with hot water, and each variety acquires a definite taste according to the processing used and, in addition, is a drink widely consumed throughout the world. This work presents an investigation of the specific concentrations of 226Ra, 228Ra and 40K in 24 tea samples used by the Brazilian population and the associated effective dose. Tea samples were dried for six hours in a 60° C oven and placed in 200 ml polyethylene pots weighed with weighting machine model Gehaka BG 4000 and sealed to achieve the secular radioactive equilibrium condition. Teas samples were measured using the gamma spectrometry technique using high purity germanium detector (HPGe) and with the LabSOCS software to calculate the efficiency curve. The counting time used to acquire the sample spectra was 30.000 seconds. The specific activity values for 40K ranged from 184 ± 56 Bq. kg-1 Lemongrass (Cymbopogon citratus) and 1087 ± 40 Bq. kg-1 for Burdock (Arctium lappa). For the 226Ra the specific activity values ranged from <4 to <27 Bq. kg-1 . For the 228Ra the specific activity values ranged from 2 ± 1 to 27 ± 3 Bq.kg-1. The effective doses ranged from 1.14 μSv / year to 18.63 μSv / year. The values presented in this study were lower than the annual average effective dose of ingestion for adults.